2008
DOI: 10.2527/jas.2007-0155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extruded linseed on growth, carcass composition, and meat quality of slaughtered pigs at one hundred ten and one hundred sixty kilograms of liveweight1

Abstract: ABSTRACT:The Western diet is characterized by a high intake of SFA relative to PUFA, and the consumption of n-3 PUFA is decreased relative to n-6 PUFA. Therefore, there has been much interest in recent years in ways to manipulate the fatty acid composition of meat. The objective of this work was to determine the effects of dietary extruded linseed, an n-3 PUFA source, on growth performance, carcass composition, meat quality, and oxidative stability of pigs slaughtered at 111.0 (±4.8) kg of BW and 160.0 (±9.2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
53
6
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 41 publications
19
53
6
9
Order By: Relevance
“…The growth performances were not modified by the introduction of n-3 fatty acids into the animal feed, which confirmed similar studies carried out with the addition of other fats than hemp such as linseed (Corino et al, 2008;Kouba et al, 2003;Matthews et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The growth performances were not modified by the introduction of n-3 fatty acids into the animal feed, which confirmed similar studies carried out with the addition of other fats than hemp such as linseed (Corino et al, 2008;Kouba et al, 2003;Matthews et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…This can be explained by the fact that these animals also had a high deposition of LA provided by the hemp oil. The value of this ratio is higher than that of other studies using linseed (7 vs. 4 to 5) (Corino et al, 2008;Guillevic et al, 2009) and also higher than the ANSES guidelines which recommend a ratio of 5 (ANC). But these animals receiving rapeseed or hemp oils had a ratio decreased by 2 in comparison with animals receiving standard feed; so this leads to better food balance for human consumption.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The higher C18:2 content of the BF of lighter pigs found in this research agrees with data Peinado, Serrano, Medel, Fuentetaja and Mateos of Serrano et al (2009b) who reported a negative correlation between BF thickness and the unsaturation of BF. In this respect, Corino et al (2008) have shown that the proportion of C18:2 in BF was lower in pigs slaughtered at 160 kg BW than in pigs slaughtered at 110 kg BW.…”
Section: Carcass Traitsmentioning
confidence: 91%